PENGARUH INVESTMENT OPPORTUNITY SET (IOS), LIKUIDITAS, DAN LEVERAGE TERHADAP KUALITAS LABA (Studi pada Industri Sektor Properti dan Real Estate yang terdaftar di Bursa Efek Indonesia periode 2013-2017) - Arshendy Graha; Khairunnisa Khairunnisa (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2018)
The sales performance of property and real estate companies in Indonesia deteriorated due to uncertain interest rates. Investors, creditors and corporate stakeholders, in this case, especially property and real estate companies, depend on the quality of earnings that have generated by the company. The high quality of earnings reflect sustained earnings for a long period of time. This study aims to examine the influence of investment opportunity set, liquidity, and leverage on earnings quality in property and real estate companies listed on the Indonesia Stock Exchange (IDX). The sampling method uses purposive sampling method with a total sample of 41 companies and a research period of 5 years so that the number of sample units are 205 data. The data analysis technique uses descriptive statistics and hypothesis testing using panel data regression analysis using the Eviews 10 software application. The test results obtained from this study simultaneously displays that investment opportunity sets, liquidity, and leverage have significant influence to earnings quality. Partially the investment opportunity set does not have a significant effect on earnings quality, liquidity has a negative effect on earnings quality, leverage does not have a significant effect on earnings quality.